Historical biogeography of the Andean region: evidence from Listroderina (Coleoptera: Curculionidae: Rhytirrhinini) in the context of the South American geobiotic scenario - Donato, Mariano Humberto (2003)
The weevil subtribe Listroderina belongs in the tribe Rhytirrhinini (subfamily Cyclominae), and has 25 genera and 300 species in the Americas. The distributional history of this subtribe was reconstructed applying dispersal-vicariance analysis (DIVA) using its genera as terminals. The results suggest that Listroderina originated within an area presently represented by the Central Chile, Paramo, Puna, Patagonia and Subantarctic subregions of the Andean region. Posteriorly, the subtribe was affected by extinctions and was confined to Central Chile, Paramo and Subantarctic subregions. Later, extinctions and dispersals took place and the subtribe was restricted to the Paramo and Puna subregions. From there, a dispersal event to the Subantarctic subregion occurred, enlarging again the geographical range of the subtribe. Subsequently, a vicariant event separated the Puna and Paramo subregions from the Subantarctic one. While the Macrostyphlus generic group was confined to the Paramo and Puna subregions and from there dispersed to other areas, the Antarctobius, Falklandius, Listronotus, and Listroderes generic groups diversified in the Subantarctic subregion. The results obtained by DIVA may be linked to major geological events of South America. Thus, the geobiotic scenarios recorded in this subcontinent since the late Cretaceous could be used to interpret the biogeographical events which drove Listroderina evolution.